Multivariate regression analysis of prime variables affecting ophthalmic patients' satisfaction in a resource limited economy - Emmanuel Olu Megbelayin; Jacob Sackey (PAGEPress Publications, 2014)
The aim of the present study was to appraise prime dependent variables of ophthalmic patients' satisfaction in a Nigerian public eye care facility with a view to boosting service uptake. It was a cross sectional study conducted between March and May 2012 in our centre. Consecutive clinic patients (n=251) that met study's criteria were recruited. The patients filled interviewer-administered structured questionnaires. A total of 251 patients were analyzed comprising 139 males (55.4%) and 112 females (44.6%). Male:female ratio=1:0.8. The ages of the patients studied ranged from 17 to 92 years with a mean of 37.2 years±15.57. Bivariate analysis, validated by multiple logistic regression, showed P values of 0.021, 0.008, 0.036, 0.008 and 0.004 for privacy, comfort during eye exam, fairness (non-partiality), thoroughness of examination and expectation, respectively. Satisfaction with overall quality of services was 80.1%. The services of any eye facility should be patient-driven to attain desired goals; therefore the identified areas of patients' dissatisfaction should be addressed for effective service uptake.